2006
DOI: 10.1002/jsfa.2507
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the meat quality of veal

Abstract: Over the last 50 years the veal industry has seen a number of changes, in particularly in production systems with the introduction and acceptance of grain-fed and heavier calves and the progressive move from individual pens to group housing. Reasons for the changes are multi-faceted of which two important players are the well-being of the animal and the public perception of the industry. Regardless of the reasons for the changes, breeders strive to attain veal conforming to the rigorous standards reflecting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 76 publications
0
20
1
Order By: Relevance
“…On the other hand, initial WB shear force in the current experiment was greater than obtained from calves of the same breed in earlier studies (Vieira et al, 2005). The rate of tenderization of veal is the same as that of beef, although veal is usually more tender than beef (Ngapo & Gariepy, 2006). In this sense, a similar rate of tenderization, but greater WB values, was found in beef from young bulls of the same breed Blanco et al, 2009Blanco et al, , 2010 than found in FIN and SUP of the present experiment.…”
Section: 3contrasting
confidence: 64%
“…On the other hand, initial WB shear force in the current experiment was greater than obtained from calves of the same breed in earlier studies (Vieira et al, 2005). The rate of tenderization of veal is the same as that of beef, although veal is usually more tender than beef (Ngapo & Gariepy, 2006). In this sense, a similar rate of tenderization, but greater WB values, was found in beef from young bulls of the same breed Blanco et al, 2009Blanco et al, , 2010 than found in FIN and SUP of the present experiment.…”
Section: 3contrasting
confidence: 64%
“…Significant differences ( P < 0.001) in the lightness ( L *) and yellowness ( b *) of the cuts were observed. Anatomical location and proportions of red fibres are considered the main causes of the differences between meat cuts: dark muscles have a higher proportion of red fibres than light muscles. The ER had greater lightness than the other hindquarter cuts (45.80 versus 42.60, 41.77, 40.98 and 35.62 for KK, IR, BR and HR cuts, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Basically, consumers are believed to assess veal quality on the lean color [6]. For meat color, CIE L* (lightness) of both muscles for the 5 month group were higher than those for the 8 month groups.…”
Section: Resultsmentioning
confidence: 99%
“…According to Council Regulation (EC) No 361/2008 of April 14th [5], veal is described as the meat from unweaned calves that are slaughtered when they are no more than 8 months old. The European Commission differentiates veal as meat derived from calves of 16–19 week of age [6]. Currently, young Holstein bulls have been problematic for a livestock raiser in Korea.…”
Section: Introductionmentioning
confidence: 99%